A Dual-Plasmid-Based CRISPR/Cas9-Mediated Strategy Enables Targeted Editing of pH Regulatory Gene pacC in a Clinical Isolate of Trichophyton rubrum - Sanchita Sanchaya Dey; Sivaprakash Ramalingam; Bhupesh Taneja (Journal of Fungi, 2022)
Trichophyton rubrum is the most prevalent causative agent responsible for 80–90% of all known superficial fungal infections in humans, worldwide. Limited available methods for genetic manipulations have been one of the major bottlenecks in understanding relevant molecular mechanisms of disease pathogenesis in T. rubrum. Here, a dual-plasmid-based CRISPR/Cas9 strategy to edit pH regulatory transcription factor, pacC, of a clinical isolate of T. rubrum by non-homologous end joining (NHEJ) repair is presented. A cas9–eGFP fusion that aids pre-screening of primary transformants through detection of GFP fluorescence is expressed from one plasmid while target-specific sgRNA from the other brings about mutagenesis of pacC with an overall efficiency of 33.8–37.3%. The mutants had reduced transcript levels of pacC at both acidic and alkaline pH with several morphological abnormalities. We believe this dual-plasmid-based CRISPR/Cas9 strategy will aid functional genomics studies, especially in non-lab-adapted clinical strains of T. rubrum.